Interventions for the prevention of musculoskeletal disorders in a seasonal work context: A scoping review. (July 2021) - Major, Marie-Eve; Clabault, Hélène; Wild, Pascal
Abstract: Seasonal work is characterized by difficult working conditions further influenced by organizational, physical, and time constraints which expose seasonal workers to high risks of MSDs. Our aim was to provide an overview of the recommendations and interventions carried out in a seasonal work context to prevent MSDs. To do this, we conducted a scoping review through a systematic electronic search of seven scientific databases and the websites of ergonomics and occupational health and safety organizations. After screening by independent reviewers according to specific criteria sets, we performed qualitative analyses on the 16 studies retained. Findings revealed six categories of transformation targets sought by the interventions/recommendations with the technical devices/physical work environment category being the most reported. We also found it was quite rare for studies to consider the seasonal work context in and of itself when developing and implementing interventions. Our review thus highlights the need to pay attention to intervention processes in order to better understand the influence of seasonality on the measures taken to prevent MSDs in working environments. Highlights: - Seasonal work is demanding and exposes workers to situations at risk of MSDs. - Published interventions targeting the prevention of MSDs in a seasonal work context are rare. - Most MSD interventions conducted in a seasonal work context targeted technical devices and the physical work environment. - Most MSD interventions in a seasonal work context lack several key intervention process elements. - The influence of the seasonal work context must be considered when developing MSD research-intervention studies.